The Influence Of Entrepreneurial Knowledge, Adversity Intelligence, And Self-Efficacy On Students' Entrepreneurial Intentions - Fitriani Latief; Dirwan Dirwan; Ahmad Firman (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2024)
This research aims to find out how entrepreneurial knowledge influences entrepreneurial intentions among ITB Nobel Indonesia students; to find out how advertising intelligence influences entrepreneurial intentions among ITB Nobel Indonesia students and to find out how self-efficacy influences entrepreneurial intentions among ITB Nobel Indonesia students.This research uses a causal analysis design with quantitative research methods. The population in this study was 277 students from the ITB Nobel Indonesia management study program. Determining the sample size used the Slovin formula with simple random sampling to obtain a sample size of 73 students. The data analysis technique is to use multiple regression analysis. The research results found thatEntrepreneurship knowledge, advertising intelligence and self-efficacy towards entrepreneurial intentions among ITB Nobel Indonesia students.